2019
DOI: 10.7554/elife.47110
|View full text |Cite|
|
Sign up to set email alerts
|

A chemical probe of CARM1 alters epigenetic plasticity against breast cancer cell invasion

Abstract: CARM1 is a cancer-relevant protein arginine methyltransferase that regulates many aspects of transcription. Its pharmacological inhibition is a promising anti-cancer strategy. Here SKI-73 (6a in this work) is presented as a CARM1 chemical probe with pro-drug properties. SKI-73 (6a) can rapidly penetrate cell membranes and then be processed into active inhibitors, which are retained intracellularly with 10-fold enrichment for several days. These compounds were characterized for their potency, selectivity, modes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 69 publications
1
31
0
Order By: Relevance
“…Keeping this substitution in designing future nsp14 inhibitors will provide selectivity against PKMTs. WZ16 42 and compound 8 are PRMT4 (CARM1) inhibitors. Although compound 8 is a relatively weak nsp14 inhibitor (IC 50 = 95 ± 6 µM), it is likely cell permeable (US20180305391A1).…”
Section: Discussionmentioning
confidence: 99%
“…Keeping this substitution in designing future nsp14 inhibitors will provide selectivity against PKMTs. WZ16 42 and compound 8 are PRMT4 (CARM1) inhibitors. Although compound 8 is a relatively weak nsp14 inhibitor (IC 50 = 95 ± 6 µM), it is likely cell permeable (US20180305391A1).…”
Section: Discussionmentioning
confidence: 99%
“…This degree of selectivity provides a promising framework for the development of higher potency chemical probes for cellular assays. Interestingly, nine structures have recently been added to the PDB of CARM1 from Mus musculus in complex with different aromatic-containing bisubstrate inhibitors (PDB codes 5TBJ, 5TBI, 5TBH, 5LV3, 5LV2 [36] and 5ISB 5IS9, 6DVR and 6D2L [38]). Superposition of these structures with the CARM1-9 complex structure (Supplementary Figure S9) revealed reasonably good overlap of 9's aminopyridine group with the aromatic groups of these inhibitors, particularly in the SAM carboxylate binding pocket (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Design of selective inhibitors is challenging however, since the residues involved in SAM and substrate arginine binding are largely conserved in the nine PRMTs encoded in the human genome, particularly between type I family members [37]. In line with recent advances [38], the development and structural investigation of rationally designed bisubstrate inhibitors remains a desirable route to identify individual residue variations that may contribute to selective inhibition of CARM1 over PRMT1 for example. (B) Structures of bisubstrate azo-SAM inhibitors from the present study (4-10) and those reported previously by van Haren et al [28,33].…”
Section: Introductionmentioning
confidence: 99%
“…They found that small subclones of breast cancer cells expressing IL11 and vascular endothelial growth factor D (VEGFD) synergistically promoted metastasis, among which scRNA-seq of CD45+ cell populations from primary tumors, blood, and lungs showed that IL11 acts on bone marrow-derived mesenchymal stromal cells and induces pretumorigenic and premetastatic neutrophils to promote the progression of tumor metastasis 36 . In addition, Cai et al 37 proposed the chemical probe arginine methyltransferase CARM1 to combat the invasion of breast cancer cells by changing epigenetic plasticity using scRNA-seq. The study revealed that high heterogeneity caused by genetic and epigenetic characteristics of cancer subsets serves as a mechanism to promote tumor metastasis.…”
Section: Identifying the Characteristics Contributing To Breast Cancer Metastasis By Scrna-seqmentioning
confidence: 99%